Proximal Tubule-Specific Deletion of the NHE3 (Na+/H+ Exchanger 3) in the Kidney Attenuates Ang II (Angiotensin II)-Induced Hypertension in Mice. Issue 3 (September 2019) - Li, Xiao C.; Zhu, Dongmin; Chen, Xu; Zheng, Xiaowen; Zhao, Chunling; Zhang, Jianfeng; Soleimani, Manoocher; Rubera, Isabelle; Tauc, Michel; Zhou, Xinchun; Zhuo, Jia L.
Abstract : The present study directly tested the hypothesis that the NHE3 (Na + /H + exchanger 3) in the proximal tubules of the kidney is required for the development of Ang II (angiotensin II)-induced hypertension using PT- Nhe3 −/− (proximal tubule-specific NHE3 knockout) mice. Specifically, PT- Nhe3 −/− mice were generated using the SGLT2-Cre / Nhe3 loxlox approach, whereas Ang II-induced hypertension was studied in 12 groups (n=5–12 per group) of adult male and female wild-type (WT) and PT- Nhe3 −/− mice. Under basal conditions, systolic blood pressure, diastolic blood pressure, and mean arterial blood pressure were significantly lower in male and female PT- Nhe3 −/− than WT mice ( P <0.01). A high pressor, 1.5 mg/kg per day, intraperitoneal or a slow pressor dose of Ang II, 0.5 mg/kg per day, intraperitoneal for 2 weeks significantly increased systolic blood pressure, diastolic blood pressure, and mean arterial blood pressure in male and female WT mice ( P <0.01), but the hypertensive response to Ang II was markedly attenuated in male and female PT- Nhe3 −/− mice ( P <0.01). Ang II impaired the pressure-natriuresis response in WT mice, whereas proximal tubule-specific deletion of NHE3 improved the pressure-natriuresis response in Ang II-infused PT- Nhe3 −/− mice ( P <0.01). AT1 receptor blocker losartan completely blocked Ang II-induced hypertension in both WT and PT- Nhe3 −/− mice ( P <0.01). However, inhibition of nitric oxide synthase with L-N G -Nitroarginine methyl ester had no effect on Ang II-induced hypertension in WT or PT- Nhe3 −/− mice (not significant). Furthermore, Ang II-induced hypertension was significantly attenuated by an orally absorbable NHE3 inhibitor AVE0657. In conclusion, NHE3 in the proximal tubules of the kidney may be a therapeutical target in hypertension induced by Ang II or with increased NHE3 expression in the proximal tubules. Abstract : Supplemental Digital Content is available in the text.